The degree of mucosal damage to the small intestine and serum immunoglobulin G4 levels correlate with celiac disease. Issue 7 (July 2015) - Demirci, Hakan; Polat, Zulfikar; Ozturk, Kadir; Kekilli, Murat; Kantarcioglu, Murat; Sahiner, Fatih; Uygun, Ahmet; Bagci, Sait
Abstract : Background: Celiac disease (CD) is an immune-mediated and chronic inflammatory enteropathy, triggered by the ingestion of gluten in genetically susceptible individuals. Immunoglobulin G4 (IgG4)-related diseases are a recently defined emerging clinical condition, characterized by increased serum IgG4 concentrations. The aim of this study was to investigate whether IgG4 levels correlate with the titers of intestinal antibodies and the degree of mucosal damage in CD patients. Materials and methods: A total of 41 CD patients and 28 healthy controls were included in the study. All patients underwent a duodenal biopsy and were then diagnosed with the modified Marsh classification. Blood samples were obtained for IgG4 measurements. Serums were kept at −80°C until the analysis was carried out and plasma IgG4 levels were determined using an enzyme-linked immune sorbent assay method with a diagnostic cutoff value of 135 mg/dl. Results: The mean age of the CD and the control group was 26.8±8.3 and 26.9±6.2 years, respectively. The mean IgG4 levels were significantly higher in CD patients (283.21±39.02 mg/dl) compared with the healthy control group (68.97±15.89 mg/dl, P <0.0001). In the CD group, 27/41 patients and in the control group, 4/28 patients had high IgG4 levels (>135 mg/dl, P <0.0001). A close correlation was found between the grade of mucosal damage, IgG4 levels, and antigliadin-IgA; the higher the grade Marsh score, the higher the measured IgG4 ( P <0.05). Conclusion: In our study, IgG4 levels of CD patients were higher than normal ranges whereas the results of the control group were within physiologic limits. We also showed for the first time that there was a correlation between IgG4 levels, autoantibody, and severity of mucosal damage. To the best of our knowledge, this is the first study to evaluate IgG4 levels and mucosal damage in CD patients.